Limiting dilution analysis of helper T-cell function. II. An approach to the study of the function of single helper T cells. - Waldmann, H; Pope, H; Lefkovits, I (1976)
Procedures have been described which are suitable for experiments utilizing a microculture system whereby one can easily study the function of single helper T cells. These are: (a) the elimination of the background anti-hapten response by preliminary anti-theta + guinea-pig complement complement treatment of the 'hapten-primed' population; (b) the removal of any contaminating hapten-specific B cells from the carrier-primed population by passage through nylon wool; (c) irradiation of long-term primed 'nylon wool' enriched helper cells tp prevent cell division; (d) the partition of individual helper cells by limiting dilution.